Réponses

2014-04-09T14:42:30+02:00
Bonjour
Fonction affine veut dire de forme   f(x) = ax+b 
on a 
f(2) = -8                                et                   f(-2) = 12 
a(2)+b = - 8                           et                    a(-2) +b = 12 
2a + b = - 8                          et                     b = 12 + 2a  on remplace dans la première
2a + 12 + 2a = - 8                  et                     b = 12 + 2a 
4a = -8-12                             et                      b = 12 + 2a
a = -20/4 = -5   on remplace dans la seconde    b = 12+2(-5) = 2 
on a la fonction qui est 
f(x) = -5x + 2